Synergistic Effects of Fructose and Food Preservatives on Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): From Gut Microbiome Alterations to Hepatic Gene Expression - Hrncir, Tomas; Trckova, Eva; Hrncirova, Lucia (Nutrients, 2024)
Background/Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD) is a growing global health problem closely linked to dietary habits, particularly high fructose consumption. This study investigates the combined effects of fructose and common food preservatives (sodium benzoate, sodium nitrite, and potassium sorbate) on the development and progression of MASLD. Methods: We utilized a human microbiota-associated mouse model, administering 10% fructose with or without preservatives for 11 weeks. Liver histology, hepatic gene expression (microarray analysis), biochemical markers, cytokine profiles, intestinal permeability, and gut microbiome composition (16S rRNA and Internal Transcribed Spacer (ITS) sequencing) were evaluated. Results: Fructose and potassium sorbate synergistically induced liver pathology characterized by increased steatosis, inflammation and fibrosis. These histological changes were associated with elevated liver function markers and altered lipid profiles. The treatments also induced significant changes in both the bacterial and fungal communities and disrupted intestinal barrier function, leading to increased pro-inflammatory responses in the mesenteric lymph nodes. Liver gene expression analysis revealed a wide range of transcriptional changes induced by fructose and modulated by the preservative. Key genes involved in lipid metabolism, oxidative stress, and inflammatory responses were affected. Conclusions: Our findings highlight the complex interactions between dietary components, gut microbiota, and host metabolism in the development of MASLD. The study identifies potential risks associated with the combined consumption of fructose and preservatives, particularly potassium sorbate. Our data reveal new mechanisms that are involved in the development of MASLD and open up a new avenue for the prevention and treatment of MASLD through dietary interventions and the modulation of the microbiome.
Keywords: myši; Mice, Inbred C57BL; mužské pohlaví; Male; synergismus léků; Food Preservatives; Gene Expression; Fatty Liver; modely nemocí na zvířatech; exprese genu; potravinářské konzervační látky; Sorbic Acid; myši inbrední C57BL; játra; střevní mikroflóra; fruktosa; Animals; Mice; zvířata; Drug Synergism; Fructose; ztučnělá játra; Liver; Disease Models, Animal; kyselina sorbová; Gastrointestinal Microbiome